Development of sustainable polymeric membranes produced with green solvents - Andreza Przygodzinski Cardoso; Alexandre Giacobbo; Carlos Arthur Ferreira (REM: International Engineering Journal)
Abstract Polymeric membrane separation technologies have gained widespread prominence in many applications, including water and wastewater treatment to remove contaminants of emerging concern (CEC). These technologies can be recognized as sustainable separation techniques due to their scalable potential and low energy consumption. However, the membranes are usually prepared with organic solvents such as N-methyl-2-pyrrolidone (NMP) and dimethylacetamide (DMAc), which are toxic and harmful to the environment and human health. Furthermore, these solvents are being banned in some countries and included on lists of substances of high concern. Therefore, finding environmentally sustainable solvents (green solvents) to produce “green membranes” has been a matter of great interest. The objective of the present study is the development of porous membranes, prepared with green solvents, Cyrene (Cyr) and γ-Valerolactone (GVL). The membranes were prepared by the phase inversion technique using Polysulfone (PSF), Polyvinylpyrrolidone (PVP) and Cyr or GVL or a mixture of both solvents. In this work, it was possible to produce membranes with both green solvents, as well as using a mixture of them. The membranes were characterized and tested for removing a CEC (Rosuvastatin) from water. Rosuvastatin rejection of 80% was achieved for membranes produced with a mixture of green solvents Cyr and GVL. These results are promising, as they make the membrane production process more sustainable as recommended by the 2030 Agenda through the 17 SDGs.